Effect of Partial Substitution of Beef with White Oyster Mushroom (Pleurotus ostreatus) on Nutritional Profile and Sensory Quality of Meatball Products - If'all, If'all; Nofrianto, Nofrianto; Spetriani, Spetriani; Sabariyah, Sitti; Fathurahmi, Siti; Indriasari, Yuanita; Asrawaty, Asrawaty (Media Publikasi Cendekia Indonesia, 2025)
The increasing consumption of processed meat products has driven innovation in the partial substitution of raw materials with healthier, functional plant-based alternatives such as white oyster mushroom (Pleurotus ostreatus). This study aimed to evaluate the effect of partially substituting beef with oyster mushrooms on the nutritional profile and sensory quality of meatball products. A quantitative approach was employed using a Completely Randomized Design (CRD) with one factor and five treatment levels (J0–J4), each replicated three times. The treatments consisted of 0 g, 25 g, 50 g, 75 g, and 100 g of oyster mushrooms combined with 300 g, 275 g, 250 g, 225 g, and 200 g of beef, respectively. The results showed that increasing the proportion of oyster mushrooms significantly (p < 0.05) increased moisture content (from 28.57% to 35.37%), crude fiber (from 0.80% to 3.10%), carbohydrate content (from 2.50% to 4.80%), and water-holding capacity (from 55.50% to 68.10%). Conversely, protein and fat contents decreased significantly, with protein dropping from 18.50% (J0) to 13.00% (J4), and fat from 15.80% to 7.20%. Sensory evaluation using a hedonic test with 20 semi-trained panelists revealed that treatment J2 (50 g oyster mushroom + 250 g beef) received the highest scores for taste (3.90), aroma (3.95), texture (3.85), and color (3.95). Treatments with higher levels of mushroom substitution (J3 and J4) led to a significant decline in sensory acceptance, particularly in taste and texture. Therefore, partial substitution with up to 50 g of white oyster mushroom is recommended as an optimal level to improve the nutritional quality of meatballs without compromising sensory attributes, supporting the development of healthier and more functional meat-based products.